2023
DOI: 10.3390/jcm12062373
|View full text |Cite
|
Sign up to set email alerts
|

Digital Health Technologies for Post-Discharge Care after Heart Failure Hospitalisation to Relieve Symptoms and Improve Clinical Outcomes

Abstract: The prevention of recurrent heart failure (HF) hospitalisations is of particular importance, as each such successive event may increase the risk of death. Effective care planning during the vulnerable phase after discharge is crucial for symptom control and improving patient prognosis. Many clinical trials have focused on telemedicine interventions in HF, with varying effects on the primary endpoints. However, the evidence of the effectiveness of telemedicine solutions in cardiology is growing. The scope of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…As for the HF prognosis, fundamental dilemmas on the use of this tool are still open. Many questions concern what type of patients, how, and for how long should be followed up with TM, while other unsolved issues concern who should run the tele-visits and who should intervene in emergency case [ 50 ].…”
Section: Telemedicine and Heart Failurementioning
confidence: 99%
“…As for the HF prognosis, fundamental dilemmas on the use of this tool are still open. Many questions concern what type of patients, how, and for how long should be followed up with TM, while other unsolved issues concern who should run the tele-visits and who should intervene in emergency case [ 50 ].…”
Section: Telemedicine and Heart Failurementioning
confidence: 99%
“…For instance, studies have shown that EHRs can help reduce hospital readmission rates by enabling better discharge planning and coordination of care post-discharge. By ensuring that patients receive appropriate follow-up care and support, EHRs play a crucial role in preventing avoidable readmissions (Abraham, Meng, Tripathy, Kitsiou, & Kannampallil, 2022; Krzesiński, 2023). In managing chronic diseases, EHRs facilitate the tracking and managing of patients' conditions over time, enabling healthcare providers to adjust treatment plans as needed and intervene early when patients' conditions worsen.…”
Section: Health Outcomesmentioning
confidence: 99%